Application of the Extreme Programming Method in Designing Applications for Processing Librarian Credit Scores at UPT Sriwijaya University Library - Yarza Aprizal (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2022)
Taking care of the administration of the librarian's credit score is a mandatory thing that a librarian must do in applying for a promotion. The obstacle that is often faced by librarians is collecting in physical form (letters of assignment, certificates and reports) one by one with the collection of reports still in the form of printed documents. If the assessment team requires a softcopy of the report, the assessment team will ask the librarian directly, which causes the assessment time and report documentation to be disorganized. The purpose of this research is to produce a librarian credit score processing application design that can facilitate librarians when they will carry out the administrative process in applying for promotions. This research applies the Extreme Programming method with the stages of planning, designing, coding and testing. The results of the tests carried out using the Black-box method, all functions can run as expected so that it can help the librarian to store physical evidence and determine the credit score obtained when carrying out an activity.